2022
DOI: 10.1002/jcop.22795
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of well‐being during the COVID‐19 pandemic: The importance of financial satisfaction and neuroticism

Abstract: Current research suggests that the COVID‐19 pandemic adversely impacts well‐being. This study examined how subjective well‐being (SWB) and psychological well‐being (PWB) in Singapore were affected during the pandemic, and the factors that were important to SWB. A representative sample of 999 respondents completed an online survey during the pandemic in August 2020 (after a lockdown was lifted). Two hundred and thirty‐two respondents completed the follow‐up Wave 2 survey 4 months later. Analyses showed that SWB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 46 publications
(81 reference statements)
2
13
0
Order By: Relevance
“…In line with Shokrkon and Nicoladis (2021) [51], we also found that Neuroticism was negatively and signi cantly associated with emotional, psychological and social well-being. Our results also support other studies suggesting that Neuroticism is linked to an increased number of mental health issues in general before [17,20,67], and during the pandemic [51,68,69,70,71].…”
Section: Neuroticismsupporting
confidence: 91%
“…In line with Shokrkon and Nicoladis (2021) [51], we also found that Neuroticism was negatively and signi cantly associated with emotional, psychological and social well-being. Our results also support other studies suggesting that Neuroticism is linked to an increased number of mental health issues in general before [17,20,67], and during the pandemic [51,68,69,70,71].…”
Section: Neuroticismsupporting
confidence: 91%
“…Our results demonstrate that the most powerful advantage of the path analysis is that it has the ability to identify indirect effects.Childhood abuse is associated with higher neuroticism (11,12,13). Furthermore, neuroticism is closely associated with subjective well-being (14,15,30). Even during the COVID-19 pandemic, extraversion was not signi cantly correlated with well-being, whereas neuroticism remained strongly associated with lower well-being (31).…”
Section: Discussionmentioning
confidence: 99%
“…Maltreatment in childhood is known to be a risk factor for psychopathology in both childhood and adulthood, and various types of maltreatment in childhood have been suggested to be associated with the severity of psychological distress in adulthood (10). Furthermore, childhood maltreatment in addition to inadequate parenting is associated with high neuroticism (11,12,13), and neuroticism is also associated with reduced well-being (14,15). Among the various personality traits, neuroticism is a major candidate as a predisposing factor of several mental disorders (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Greater psychological distress symptoms were also more pronounced for individuals who score higher in neuroticism, possibly due to their greater fear of the pandemic (Aschwanden et al, 2021;Starcevic & Janca, 2022). Following individuals for four months, Ng and Kang (2022) showed that neuroticism was one of the most consistent predictors of social well-being during the pandemic. Earlier higher neuroticism associated with future lower life satisfaction and positive feelings, and higher negative feelings.…”
Section: Introductionmentioning
confidence: 95%